Cyberbullying Phenomenon of High School Students: An Exploratory Study in West Kalimantan, Indonesia - William Vincent Setiawan; Vernawati Eva Fitrisna; Fairuz Michellianouva; Celly Septine Mayliza (Bina Nusantara University, 2020)
Cyberbullying became a common occurrence among teenagers in the world today. The aim of research was to explore the cyberbullying experience of high school students in West Kalimantan. The research was conducted to identify internet usage and online activities that led to cyberbullying victimization. The methods used a questionnaire collected during June 2019 from 50 students (25 males and 25 females) graded 10 to 12, and used a one-way ANOVA analysis. Significant gender differences were found which indicated that boys were more often involved in cyberbullying both as the perpetrator and the victim. Students with lower academic achievement tend to be online perpetrators than students with better academic performance. The research investigated how cyber oppression impacts both as a perspective of victimization and persecution, discussing the practice of reporting students to parents, school officials and other adults. Parental and teacher supervision as a strategy reduces student involvement in cyberbullying and generates awareness among students. The result implies that schools have an important role in teaching cybersecurity, adding cyberbullying subject in the curriculum, and sharing experiences with students.